Cognitive Profile and Its Evolution in a Cohort of Multiple System Atrophy Patients - Sambati, Luisa; Calandra-Buonaura, Giovanna; Giannini, Giulia; Cani, Ilaria; Provini, Federica; Poda, Roberto; Oppi, Federico; Stanzani Maserati, Michelangelo; Cortelli, Pietro (Frontiers in Neurology, 2020)
Introduction: Cognitive decline is not a characteristic feature of multiple system atrophy (MSA), but recent still recently evidence suggests cognitive impairment as an integral part of the disease. We aim to describe the cognitive profile and its progression in a cohort of patients with MSA. Methods: We retrospectively selected patients referred to our department with a clinical diagnosis of MSA who were evaluated at least once a year during the course of the disease and underwent a comprehensive neuropsychological evaluation. Results: At the first evaluation (T0), 37 out of 60 patients (62%) were cognitively impaired, mainly (76%) in attention and executive functioning. Thirteen 13 patients were impaired in one cognitive domain and 24 in more than one cognitive domain. Seventy-six percent 76% were selectively impaired in attention or executive functioning. Six out of the 24 had dementia were demented. Twenty patients underwent a follow-up evaluation (T1) after a mean of 16.6 ± 9.3 months from the first evaluation (T0). Eight out of 20 patients were cognitively normal both at T0 and T1. Seven out of 12 patients presented with stable cognitive impairment at T1, while cognitive decline progressed in 5 patients 5 progressed. Patients with progression in cognitive decline Progressor performed significantly worse at T0 than cognitively stable patients. Education was significantly different between patients with and without cognitive impairment. No other differences in demographic and clinical variables and autonomic or sleep disturbances were found. Patients with dementia Demented had higher age were older at disease onset and at T0 and had lower education and disease duration at T0 compared to those in other groups. Conclusions: In patients with MSA, we observed three different cognitive profiles: normal cognition, stable selective attention-executive deficits, and progressive cognitive deficits evolving to dementia. The detection of cognitive impairment in patients with suspected MSA suggests the need for comprehensive and longitudinal neuropsychological evaluation.